Peran Visum et Repertum Psychiatricum dalam Implikasi Pembuktian terhadap Kasus Kekerasan Seksual di Perguruan Tinggi - Atiyatunnajah, Megawati; Apriandhini, Megafury; Rajasa, Alvien Okta (Universitas Sebelas Maret, 2026)
Sexual violence is a form of Human Rights violation, particularly in the context of higher education, which has become a prominent issue. With numerous reports from victims, it can disrupt the educational process and the mental well-being of those affected. This research is important to understand the role of visum et repertum psychiatricum as evidence in cases of sexual violence in higher education, where this issue is increasingly urgent to address. The aim of this study is to analyze how visum et repertum psychiatricum can contribute to the evidentiary process and law enforcement against perpetrators of sexual violence. The methodology used in this research is a qualitative approach, involving document analysis and interviews with legal and psychological experts. The findings indicate that visum et repertum psychiatricum holds significant power in supporting victims' claims, providing objective evidence regarding the psychological impact experienced, and assisting judges in making fair decisions. The conclusion of this study emphasizes that the integration of visum et repertum psychiatricum in legal processes is crucial to enhance the effectiveness of handling sexual violence cases in higher education and to provide better protection for victims.